Application of blockchain methodology in secure task scheduling in cloud environment. (October 2022) - Samuel Babu, Gopatoti John; Baskar, M.
Highlights: Cloud services are greatly adapted to diverse problems of real-world computing. By accessing the cloud services independent of user location, the service data faces variety of challenges in terms of security. This article analyzes and performs detailed review on the methods of scheduling in cloud resources as well as services. Also, the security constraints are greatly explored towards the methods of data security available. Also, the article discusses the impact of blockchain methods in detail which support the maximization of QoS metrics. Abstract: Cloud services are greatly adapted to diverse problems of real-world computing. The users access various cloud services to perform variety of tasks. Such tasks are handled through the services provided by different service providers. By accessing the cloud services independent of user location, the service data faces variety of challenges in terms of security. Also, it is necessary to consider different QoS metrics of services in the sense to improve the performance of services. However, there exist many scheduling algorithms exist, they differ with the constraints considered and the result produced. This article analyzes and performs detailed review on the methods of scheduling in cloud resources as well as services. Also, the security constraints are greatly explored towards the methods of data security available. Both the corners of cloud platform are analyzed and presented in detail. Finally, the methods of scheduling and security schemes are categorized in detail. Also, the article discusses the impact of blockchain methods in detail which support the maximization of QoS metrics.